Parenting as a Nonshared Environmental Factor: A Sibling Barricade Analysis - Joyner-Carpanini, Bridget (Crime & delinquency, 2024)
Research attempting to uncover sources of nonshared environmental influences on behavioral development has highlighted the importance of differential parenting. One way in which parenting may be conceived of as a nonshared environment but has yet to be fully examined in the literature, is through sibling social comparisons. The current study addresses this gap by conducting a series of sibling barricade models examining whether adolescents are affected by their parents’ behaviors toward their siblings. Analyses of the Add Health data supported findings of prior research indicating that parenting is not consistent across siblings, but rather is individualized. Results of the sibling barricade models revealed that differences in parenting toward one child did not, however, explain differences in antisocial behavior between siblings.